2016
DOI: 10.2967/jnumed.115.166934
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment18F-FDG PET Textural Features in Locally Advanced Non–Small Cell Lung Cancer: Secondary Analysis of ACRIN 6668/RTOG 0235

Abstract: In a secondary analysis of American College of Radiology Imaging Network (ACRIN) 6668/RTOG 0235, high pretreatment metabolic tumor volume (MTV) on 18F-FDG PET was found to be a poor prognostic factor for patients treated with chemoradiotherapy for locally advanced non–small cell lung cancer (NSCLC). Here we utilize the same dataset to explore whether heterogeneity metrics based on PET textural features can provide additional prognostic information. Methods Patients with locally advanced NSCLC underwent 18F-FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 32 publications
(34 reference statements)
2
53
0
Order By: Relevance
“…Although a number of studies have included only between 20 and 70 patients [50, 71, 8692], some of the most recent studies have included between 80 and more than 200 patients: 88 patients with oropharyngeal squamous cell carcinoma [93], 103 with bone and soft tissue lesions [94], 101 with early-stage NSCLC [95], 112 with oesophageal cancer and 101 with NSCLC [60], 113 with glioma [36], 107 and 217 with oesophageal cancer [96, 97], 132 with lymph node involvement in lung cancer [98], 116, 195 and 201 with NSCLC [99101], 137 with pancreatic lesions [102], and 188 lesions in lymphoma patients [103]. Some of the most recent studies have also used more robust statistical analysis, compared to these recently reviewed [28], several of them using a machine-learning method, e.g.…”
Section: Promising Clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have included only between 20 and 70 patients [50, 71, 8692], some of the most recent studies have included between 80 and more than 200 patients: 88 patients with oropharyngeal squamous cell carcinoma [93], 103 with bone and soft tissue lesions [94], 101 with early-stage NSCLC [95], 112 with oesophageal cancer and 101 with NSCLC [60], 113 with glioma [36], 107 and 217 with oesophageal cancer [96, 97], 132 with lymph node involvement in lung cancer [98], 116, 195 and 201 with NSCLC [99101], 137 with pancreatic lesions [102], and 188 lesions in lymphoma patients [103]. Some of the most recent studies have also used more robust statistical analysis, compared to these recently reviewed [28], several of them using a machine-learning method, e.g.…”
Section: Promising Clinical Resultsmentioning
confidence: 99%
“…Some of the most recent studies have also used more robust statistical analysis, compared to these recently reviewed [28], several of them using a machine-learning method, e.g. neural networks [96], support vector machines [94, 98, 103] or the least absolute shrinkage and selection operator (LASSO) [95, 101]. The majority of these recent studies have concluded that TA can provide useful quantitative metrics regarding patient management (prognosis, response to therapy, distant metastasis prediction) in different cancer models except one that showed more mixed results [104], whereas another concluded that the improvement, although significant, may not be sufficient to have a clinical impact [97].…”
Section: Promising Clinical Resultsmentioning
confidence: 99%
“…Aerts et al built a radiomic signature consisting of a combination of four features in a retrospective lung cancer cohort, which was predictive for survival in head and neck and NSCLC independent cohorts. One textural feature calculated from GLCM, SumMean, was identified using the LASSO procedure as an independent predictor of overall survival that complements metabolic tumor volume (MTV) in decision tree . A radiomic signature was built from PET‐CT for survival after SBRT for lung cancer .…”
Section: Overview Of Research and Clinical Applications Of Cancer Radmentioning
confidence: 99%
“…43 PET tumor radiomics can help predict response in NSCLC. 44 Yang et al found that GLSZM-LZLGE exhibited significant temporal changes in partial metabolic responders. 45 Cheng et al showed that texture parameters (GLSZM-ZSV) can help predict the survival in NSCLC patients.…”
Section: D Identification Of Important Features and "Crosstalk" Frmentioning
confidence: 99%